Pneumonia in Ghana—a need to raise the profile - Abbey, M.; Afagbedzi, S.K.; Afriyie-Mensah, J.; Antwi-Agyei, D.; Atengble, K.; Badoe, E.; Batchelor, J.; Donkor, E.S.; Esena, R.et.al. (International Health, 2018)
Despite the high mortality, pneumonia retains a relatively low profile among researchers, funders and policymakers. Here we reflect on the problems and priorities of pneumonia in Ghana, briefly review the evidence base and reflect upon in-person discussions between Southampton-based authors MGH and JB and academic, clinical and policy colleagues in Ghana. The discussions took place in Accra in August 2017.
Keywords: Ghana; Health Policy; Lower Respiratory Tract Infection; Pneumonia; West Africa